The U-shaped association of serum iron level with disease severity in adult hospitalized patients with COVID-19 - Tojo, Kentaro; Sugawara, Yoh; Oi, Yasufumi; Ogawa, Fumihiro; Higurashi, Takuma; Yoshimura, Yukihiro; Miyata, Nobuyuki; Hayami, Hajime; Yamaguchi, Yoshikazu; Ishikawa, Yoko; Takeuchi, Ichiro; Tachikawa, Natsuo; et al. (Scientific reports, 2021)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that leads to severe respiratory failure (RF). It is known that host exposure to viral infection triggers an iron-lowering response to mitigate pathogenic load and tissue damage. However, the association between host iron-lowering response and COVID-19 severity is not clear. This two-center observational study of 136 adult hospitalized COVID-19 patients analyzed the association between disease severity and initial serum iron, total iron-binding capacity (TIBC), and transferrin saturation (TSAT) levels. Serum iron levels were significantly lower in patients with mild RF than in the non-RF group; however, there were no significant differences in iron levels between the non-RF and severe RF groups, depicting a U-shaped association between serum iron levels and disease severity. TIBC levels decreased significantly with increasing severity; consequently, TSAT was significantly higher in patients with severe RF than in other patients. Multivariate analysis including only patients with RF adjusted for age and sex demonstrated that higher serum iron and TSAT levels were independently associated with the development of severe RF, indicating that inadequate response to lower serum iron might be an exacerbating factor for COVID-19.